2020
DOI: 10.1177/0194599820955174
|View full text |Cite
|
Sign up to set email alerts
|

Tracheotomy in a High‐Volume Center During the COVID‐19 Pandemic: Evaluating the Surgeon’s Risk

Abstract: Objective Performing tracheotomy in patients with COVID-19 carries a risk of transmission to the surgical team due to potential viral particle aerosolization. Few studies have reported transmission rates to tracheotomy surgeons. We describe our safety practices and the transmission rate to our surgical team after performing tracheotomy on patients with COVID-19 during the peak of the pandemic at a US epicenter. Study Design Retrospective cohort study. Setting Tertiary academic hospital. Methods Tracheotomy pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Additionally, the PAPR, which was advised by several recommendations (1,12,21), was used in more than half of the procedures in our study. Other principles, including limiting the number of personnel present, ensuring complete paralysis, adequate sedation, and minimizing suction during the procedure, also help to improve protection for health care workers from SARS-CoV-2 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the PAPR, which was advised by several recommendations (1,12,21), was used in more than half of the procedures in our study. Other principles, including limiting the number of personnel present, ensuring complete paralysis, adequate sedation, and minimizing suction during the procedure, also help to improve protection for health care workers from SARS-CoV-2 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Although tracheostomy confers benefit for carefully selected COVID-19 mechanically ventilated patients, we defer the procedure in patients who require high ventilator requirements with high fractions of inspired oxygen (> 80%), significant medical comorbidities leading to poor survival, severe ARDS with a low chance of recovery. The mortality in patients with COVID-19 undergoing tracheostomy had been reported to vary from 7 to 41% in the previously published outcome studies [ 16 , 30 ]. The overall 30-day mortality in our study was 66.66%, mirroring the results of other studies that reported > 50% mortality rate for COVID-19 patients who required prolonged ventilation culminating in a tracheostomy [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that none of the Otolaryngology surgeons performing tracheotomies in this study developed SARS-CoV-2-related symptoms or positive antibody seroconversion. 24…”
Section: Tracheotomy Outcomesmentioning
confidence: 99%